Dealing with monopolies and state enterprises: WTO rules for goods and services - Aaditya Mattoo (World Trade Organization (WTO), 1997)
The objective of this paper is to assess the adequacy of multilateral rules dealing with monopolies and state enterprises, particularly in the domain of services. This paper argues that since these rules depend largely on the other obligations undertaken by Members, a variety of exemptions and exclusions have weakened the rules considerably. Furthermore, liberalization of services trade, aided by negotiations under the GATS, is leading to changes in market structure and the pattern of ownership. These changes imply that government-mandated monopolies or non-competing oligopolies are disappearing from the infrastructural services for which Article VIII of GATS is most relevant. The behaviour of dominant suppliers that often remain does not fall within the scope of Article VIII and has been addressed by creating other disciplines. The paper assesses how much emphasis needs to be placed on pro-competitive regulation to ensure competitive market conditions and argues that there is a need to strengthen Article VIII and widen its scope to deal with certain generic problems.
Keywords: F13; K33; L43; 330; monopoly; international trade; services; protection; regulation